The effect of conditional cash transfers on the prepaid and postpaid expenditures of internet and cellular services: The case of Filipino households - Caoile, Krisann Carmina G. (Animo Repository, 2022)
The increase in the use of information and communication technologies (ICT) is promising for developing economies like the Philippines, as its role in households’ economic decisions begs the question of how poor families value these services. The study answers this by delving deeper into conditional cash transfer (CCT) programs. Most existing literature dissects the impact of CCTs on increasing health, nutrition, and education expenditures; however, there is still an opportunity to assess its impact on internet and cellular services expenditures. Using the 2018 Family Income and Expenditure Survey (FIES) with the Pantawid Pamilyang Pilipino Program (4Ps) serving as the treatment, a propensity score matching methodology is applied to compare beneficiaries’ expenditures on prepaid and postpaid internet and cellular services with non-beneficiaries via Average Treatment Effects on the Treated (ATT). The researchers found that being a 4Ps beneficiary does not significantly affect spending on internet connection services, postpaid cellular phone subscriptions, payment for prepaid communication, and the total of these three variables when compared to non-beneficiaries.